EMOTIONAL INTELLIGENCE IN SPEAKING CLASS AT MADURA UNIVERSITY - Mentari, Sayu in Puja; Zumam, Wildona (The Ellite of Unira, 2025)
Emotional intelligence is the ability to improve thinking and understanding of interpersonal dynamics through incorporating intelligence, empathy, and emotion in everyday life. emotions will give adverse effects on an individual if the emotions are not being controlled properly. Therefore, this study aims to describe the emotions that arise when students speak English and how students can control their emotions when speaking. This study uses a qualitative descriptive method with field notes observation and questionnaires to obtain data. The informants used purposive sampling with the category of students being the most able to speak in class, resulting six English students at the Madura University as the sample. The results of this study are the characteristics of the emotions that exist in students in the form of positive emotions and negative emotions. Negative emotions in students are fear, lack of confidence, anxiety, and shyness when speaking English. while the positive emotion of students are smile and enjoy. they regulate their emotions with the five aspects of emotional intelligence. self-awareness, self-regulations, motivation, empathy, and social skills.